THE IMPACT OF GEOPHYSICAL WEAPONS ON ENDANGERING OF ENVIRONMENT FOR THE PURPOSES OF WAR - Stajić, Ljubomir; Vujić, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The environment has considerably been damaged due to numerous destructive impacts of obsolete and dirty technologies, heavy and uncontrolled traffic, arms race, military actions, terrorist acts and other activities which are all seriously disturbing the existing balance of nature and endangering human life at the same time. There have been ominous warnings about the situation. Rapid increase in techniques of geophysical engineering and so-called geophysical weapons which their practical threats to the mere physical existence of the wild life and of human society has created a need for this exceptionally important field to be legally regulated and sanctioned by international standards. The aim of their pursuit and study is for the man to protect and improve the environment in order to save it as on integral and crucial part of human work, life and sheer existence. Over the history of human society and of scientific and technological development, implementation of learning in different fields of human activities have caused ground breaking discoveries but at the some time and aspiration to control natural processes and phenomena such as the weather, climate, earthquake, tsunami, drought, cloudiness, precipitation etc. Starting from the fact that protection of the environment is a most fundamental postulate in the best national interests of each country, a conclusion can be made that only a deep radical change in man’s attitude towards natural world with its processes and with its laws can secure further development of mankind. In respect of that, understanding and adoption of the findings and the effects of so-called geophysical weapons that have been made in this field so far have must relevant part. Namely, results and findings of the research still have not provided answers to a great number of questions. This paper examines exceptionally complex interaction between changes in nature in terms of the climate, weather etc. deliberate influence on these processes for the sake of his needs in war. The arsenal of such weapons may cause troubles on a global scale that would include not only destructive impact of various types of pollution but impoverishing natural sources, problems in demography, urban chaos, a huge discrepancy between production and distribution of goods and services and many other problems as well.